Anion and Cation Dynamics in Polyhydroborate Salts: NMR Studies - Alexander V. Skripov; Alexei V. Soloninin; Olga A. Babanova; Roman V. Skoryunov (Molecules, 2020)
Polyhydroborate salts represent the important class of energy materials attracting significant recent attention. Some of these salts exhibit promising hydrogen storage properties and/or high ionic conductivities favorable for applications as solid electrolytes in batteries. Two basic types of thermally activated atomic jump motion are known to exist in these materials: the reorientational (rotational) motion of complex anions and the translational diffusion of cations or complex anions. The present paper reviews recent progress in nuclear magnetic resonance (NMR) studies of both reorientational and diffusive jump motion in polyhydroborate salts. The emphasis is put on sodium and lithium closo-borates exhibiting high ionic conductivity and on borohydride-based systems showing extremely fast reorientational motion down to low temperatures. For these systems, we discuss the effects of order–disorder phase transitions on the parameters of reorientations and diffusive jumps, as well as the mechanism of low-temperature rotational tunneling.